Comparison of extraction efficiencies for water-transportable phenols from different land uses. (December 2016) - Williams, Jonathan S.; Dungait, Jennifer A.J.; Bol, Roland; Abbott, Geoffrey D.
Highlights: SPE followed by detection with TMAH thermochemolysis is identified as the approach to isolate/quantify water-transportable phenols. A considerable proportion of waterborne lignin is lost from soil as oligomers. Neither grazed grassland nor woodland selectively exported more phenols as a proportion of DOC. Abstract: The composition and quantification of vascular plant-derived phenols in dissolved organic matter (DOM) is of importance in understanding and estimating carbon flux from soils under different land uses. Solid phase extraction (SPE) was used to extract waterborne organic matter (WBM), and thermally assisted hydrolysis (THM) using tetramethylammonium hydroxide (TMAH) was compared with gas chromatography-flame ionization detection (GC-FID) for the quantification of oxygenated aromatics in WBM, from freshwater samples from grazed grassland, woodland and moorland land uses in southwest England, UK. WBM recovered with SPE correlated with water total organic carbon (TOC) content. SPE followed by THM was shown to be the approach for isolating and quantifying water-transportable phenols. All the different land uses exported similar amounts of lignin per unit weight of OC to the drainage water. We also conclude that a significant proportion of lignin phenols is lost from soils as a component of WBM in a particulate form, so the magnitude of total phenol loss is likely greater than previously thought.